STRUCTURE OF ORGANIZING STUDENTS' INDEPENDENT LEARNING ACTIVITIES IN HIGHER EDUCATIONAL INSTITUTIONS - Shohista Rustamova (Modern American Journals, 2025)
This article analyzes the main components of the effective organization of students' independent learning activities in higher education institutions. The theoretical and practical aspects of independent learning are considered, its structure, technological support capabilities, and strategies for guiding students to independent learning are highlighted. In addition, methodological recommendations have been developed to improve the effectiveness of independent learning.
Keywords: Independent learning, technological support, higher education, component, methodology, platform, digital learning environment, independent learning tasks, motivation.